2003
DOI: 10.1034/j.1600-0579.2003.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Percutaneous Electrical Nerve Stimulation for the Treatment of Chronic Low Back Pain in Older Adults

Abstract: This preliminary study suggests that PENS may be a promising treatment modality for community-dwelling older adults with CLBP, as demonstrated by reduction in pain intensity and self-reported disability, and improvement in mood, life control, and physical performance. Larger studies with longer duration of follow-up are needed to validate these findings and support the use of PENS in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 66 publications
1
36
1
2
Order By: Relevance
“…147 It has been used as an outcome measure in clinical trials of diverse treatments, including rehabilitation, 2,148 physical exercise, 82 percutaneous electrical nerve stimulation, 152 pharmacological treatments, 67,116 radiofrequency lesioning, 53,150 and psychological treatments. 137 To date, no studies have used anchor-based methods to examine criteria from clinically important changes on the MPI Interference Scale.…”
Section: Multidimensional Pain Inventory Interference Scalementioning
confidence: 99%
“…147 It has been used as an outcome measure in clinical trials of diverse treatments, including rehabilitation, 2,148 physical exercise, 82 percutaneous electrical nerve stimulation, 152 pharmacological treatments, 67,116 radiofrequency lesioning, 53,150 and psychological treatments. 137 To date, no studies have used anchor-based methods to examine criteria from clinically important changes on the MPI Interference Scale.…”
Section: Multidimensional Pain Inventory Interference Scalementioning
confidence: 99%
“…Physical therapies such as heat, cold, ultrasound, electrical nerve stimulation, and massage therapy have been described for treatment of chronic back pain [8,10] with substantial pain relief and improved range of motion (ROM). Electrical nerve stimulation includes transcutaneous electrical nerve stimulation [15,19], interferential therapy [13,14], or percutaneous electrical nerve stimulation [22]. The efficacy of all these treatments remains controversial as few studies had an acceptable methodologic design [10,22], even if some studies indicated substantial reduction in pain intensity and pain-related disability in patients after percutaneous electrical stimulation compared with a sham group.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects randomized to PENS plus physical therapy intervention had significantly greater reductions in pain intensity measures at the end of the 6 weeks (P<.001). These pain reduction effects were maintained at 3-month follow-up [67].…”
Section: Transcutaneous Electrical Nerve Stimulationmentioning
confidence: 58%